Multicenter collaborative for orthopaedic research in India: An opportunity for global leadership - Mathew, George (Medknow Publications, 2008)
Road traffic accidents are increasing at an alarming rate and have become a major public health concern in India. In addition, there is a lack of trauma research output and reliable data from India. There are several issues and challenges that have presented an opportunity for researchers and surgeons in India to develop a collaborative aimed at improving the quality and productivity of orthopaedic trauma research. Establishing a network of surgical researchers across India is a necessary first step towards global leadership in orthopaedic surgery trials.